A Robust Adaptive Super-Twisting Sliding Mode Controller applied on grid-tied power converter with an LCL filter. (May 2022) - Hollweg, Guilherme Vieira; de Oliveira Evald, Paulo Jefferson Dias; Tambara, Rodrigo Varella; Gründling, Hilton Abílio
Abstract: This paper presents a new robust adaptive controller, totally developed on discrete-time. This controller is composed by two control structures: a Robust Model Reference Adaptive Controller (RMRAC) and an Adaptive Super-Twisting Sliding Mode (STSM) Controller, constituting a new control structure, nominated Robust Adaptive STSM Controller. The main advantage of this new control proposal is its high adaptability and robust performance, with fast reference tracking without chattering. The stability and robustness analysis, in discrete time, are presented, considering the overall plant, that is, in presence of matched and unmatched dynamics. To evaluate its robustness performance, the proposed controller is designed for grid-injected current control of three-phase grid-tied power converter with an LCL filter under weak grid. To validate it, the plant was partially modeled as a first order transfer function, neglecting capacitor dynamics and considering it as an additive dynamics on control design. Experimental results are presented to corroborate the controller performance and the stability analysis by means of Lyapunov Theory is provided.